## 2. sin(6x – $\frac{\pi}{3}$ ) = cos(x – $\frac{\pi}{6}$ )

Question

2. sin(6x – $\frac{\pi}{3}$ ) = cos(x – $\frac{\pi}{6}$ )

in progress 0
2 years 2020-11-14T02:37:20+00:00 2 Answers 61 views 0

## Answers ( )

1. 2. $sin(6x – \frac{\pi}{3}) = cos(x – \frac{\pi}{6})$

$⇔sin(6x – \frac{\pi}{3}) = sin(\frac{\pi}{2} – x + \frac{\pi}{6})$

$⇔sin(6x – \frac{\pi}{3}) = sin(\frac{2\pi}{3} – x)$

$⇔ \left[ \begin{array}{l}6x – \frac{\pi}{3}=\frac{2\pi}{3} – x + k2\pi\\6x – \frac{\pi}{3}=\pi – (\frac{2\pi}{3} – x) + k2\pi\end{array} \right.$

$⇔\left[ \begin{array}{l}x=\frac{\pi}{7} + k\frac{2}{7}\pi\\x=\frac{2\pi}{15}+k\frac{2}{5}\pi\end{array} \right.$ ( $k ∈ Z ) 2. Giải thích các bước giải:$\sin{\left ( 6x – \dfrac{\pi}{3} \right )} = \cos{\left ( x – \dfrac{\pi}{6} \right )}\Leftrightarrow \cos{\left ( \dfrac{\pi}{2} – 6x + \dfrac{\pi}{3} \right )} = \cos{\left ( x – \dfrac{\pi}{6} \right )}\Leftrightarrow \cos{\left ( \dfrac{5\pi}{6} – 6x \right )} = \cos{\left ( x – \dfrac{\pi}{6} \right )}\Leftrightarrow \left[ \begin{array}{l}\dfrac{5\pi}{6} – 6x = x – \dfrac{\pi}{6} + k2\pi\\\dfrac{5\pi}{6} – 6x = \dfrac{\pi}{6} – x + k2\pi\end{array} \right.\Leftrightarrow \left[ \begin{array}{l}x = -\dfrac{\pi}{7} – \dfrac{k2\pi}{7}\\x = \dfrac{2\pi}{15} – \dfrac{k2\pi}{5}\end{array} \right.\$